Mohalla Clinics in Delhi: A Preliminary Assessment of their Functioning and Coverage. Issue 2 (August 2019) - Sah, Taniya; Kaushik, Rituparna; Bailwal, Neha; Tep, Neisetuonuo
The Government of Delhi introduced the policy of Mohalla Clinics in 2015 in order to improve its health care system. It was aimed at providing primary health care to people in their neighbourhood, with a particular focus on people residing in poor localities of Delhi. This article seeks to assess the role of Mohalla Clinics in the urban health care system. Based on a primary survey conducted in various areas of Delhi, we find that these clinics have helped in easing the pressure on tertiary care hospitals by providing treatment of minor ailments within the vicinity of neighbourhood. Overall, people positively endorse this initiative which contributed to a decline in out-of-pocket expenditure on medicines and tests. We find that Mohalla Clinics are ensuring better geographical access to health services by reducing time in commuting and waiting. Their scope, however, can be further broadened by introducing provisions for pregnant and lactating women, who constitute a major section of the patients visiting these clinics.